Does Reference Group Moderate the Relationship between Behavioral Bias and Investment Decisions? - Rosa Dwiparameswari, Almanda; Siswanto, Ely (Jurnal Dinamika Ekonomi dan Bisnis, 2025)
In the process of making investment decisions, investors are required to consider several factors in order to avoid loss. The irrational decisions often made by investors have been associated with the influence of some psychological and emotional factors. Therefore, this research aimed to analyze the influence of overconfidence and loss aversion on investment decisions as well as the moderating effect of reference groups. The sample was 102 State University students in Malang City, Indonesia, and data obtained were analyzed using the Partial Least Square method. The results showed that overconfidence and loss aversion had a negative and significant influence on investment decisions. Moreover, the reference group moderated the influence of overconfidence and loss aversion bias on investment decisions. Young investors tend to have behavioral biases when investing, and these biases are exacerbated when they join a community. Early investment education is needed for young investors to improve investment literacy and improve their investment decision-making